TINJAUAN YURIDIS TERHADAP TINDAK PIDANA ABORTUS PROVOCATUS MENURUT UU NOMOR 36 TAHUN 2009 TENTANG KESEHATAN - Sonya Airini Batubara; Cindy Cindy; Widodo Saputra Hutagalung; Johannes Sahat Pangihutan Siahaan (Jurnal Darma Agung, 2020)
The term Abortion Provocatus is one type of abortion whose method is most often used to end an unwanted pregnancy, even though it is the most dangerous and high-risk method. The research method uses empirical juridical. Research is analytical descriptive. Sources of legal materials used in research are primary, secondary and tertiary legal materials. The technique of collecting data is literature study. The type of analysis used in this journal is qualitative analysis. The results of this study are that abortion is considered a crime by most Indonesian citizens because it is considered to violate human rights. Factors that occur to carry out abortions include economic factors, social factors, Hereditary disease factors, psychological factors and age factors. The regulation of abortion is contained in the Code of Criminal, Law No. 36 of 2009 concerning Health and Government Regulation Number 61 of 2014 concerning Reproductive Health confirms that prohibiting acts of abortion and sanctions is prohibited. Legal efforts in overcoming provocatus abortion have been pursued by formulating sanctions for perpetrators in the Criminal Code and applicable Health Laws.